The Authority of the Sunnah: Reflections on Modern Critique from a Qur’ānic Perspective - Khan, Izhar Ahmed (Islamic Studies, 2024)
This article delves into the reasons behind the authority of the sunnah of Prophet Muḥammad (peace be on him) as a primary source of Islamic law, while shedding light on modern critics challenging its meaning, authority, and authenticity. The exploration of the sunnah’s status involves investigating the Prophet’s position as portrayed in the Qur’ān and scrutinizing its historical authenticity through an examination of the relevant literature on Islamic learning. The analysis, aimed at elucidating the Prophet’s status from a Qur’ānic perspective, is structured around various themes, expounding the meaning and significance of the sunnah within Islamic law.